FGF23, αKLOTHO AND VITAMIN D MEDIATED CALCIUM-PHOSPHATE METABOLISM IN HEMODIALYSIS PATIENTS : FGF23, αKlotho, Vitamin D and Ca-P in Hemodialysis - Pasaoglu, Ozge Tugce; Senelmis, Ayse; Helvaci, Ozant; Derici, Ulver; Pasaoglu, Hatice (Journal of Medical Biochemistry, 2020)
Background: Klotho is a protein that acts as a co-receptor for FGF23. FGF23-Klotho axis has great importance regarding to the regulation of mineral metabolism by kidneys. In this study, we analyzed FGF23, αKlotho, 1,25-dihydroxyvitamin D3, 25-hydroxyvitamin D, parathormone, calcium and phosphate levels of hemodialysis patients in order to investigate the nature of the mineral metabolism disruption in chronic kidney diseases. Methods: Sixty hemodialysis patients and 34 healthy controls were included in the study. Serum iFGF, cFGF, soluble αKlotho were analyzed using ELISA kits. 1,25-dihydroxyvitamin D3 was determined using LC-MS/MS. Calcium, phosphate, iPTH and 25-hydroxyvitamin D were measured using autoanalyzers. Results: In hemodialysis patients, iFGF23, cFGF23, iPTH and P levels were significantly higher and 1,25-dihydroxyvitamin D3, αKlotho and Ca levels were significantly lower compared with the control group. There was no significant difference in 25-hydroxyvitamin D levels. Conclusion: Our study showed that lack of sufficient amounts of αKlotho is crucial for mineral metabolism disruptions seen as a complication of chronic kidney diseases. Despite the high levels of the hormone, FGF23 is unable to accomplish its function properly, likely due to deteriorated kidney function in hemodialysis patients.